2009
DOI: 10.1007/s00296-009-1142-x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of therapeutic efficacy in a patient with RS3PE syndrome by serologic variables and radiographic methods

Abstract: We experienced a typical patient with remitting seronegative symmetrical synovitis with pitting edema (RS 3 PE) syndrome and describe here a successful clinical course monitored by serologic variables and radiographic methods.Serum levels of interleukin-6 (IL-6), vascular endothelial growth factor (VEGF), matrix metalloproteinase-3 (MMP-3), and serum amyloid A (SAA) were remarkably elevated.Accumulation of inflammatory cells into the multiple joints was found by Gallium-67 scintigraphy.Multiple and symmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…3 It has been suggested that IL-6, MMP-3 and VEGF are key factors in the development of RS3PE syndrome and serum VEGF may be useful for the diagnosis and monitoring of disease activity. 4,5 In our case, serum levels of VEGF and IL-6 increased in parallel with the exacerbation of clinical symptoms, as described in previous reports. Nivolumab is a human immunoglobulin G4 anti-PD-1 monoclonal antibody, by which functionally exhausted T cells in the tumor microenvironment regain antitumor cytotoxicity as well as inducing various immune-related adverse events including arthritis and rheumatic disease.…”
supporting
confidence: 88%
“…3 It has been suggested that IL-6, MMP-3 and VEGF are key factors in the development of RS3PE syndrome and serum VEGF may be useful for the diagnosis and monitoring of disease activity. 4,5 In our case, serum levels of VEGF and IL-6 increased in parallel with the exacerbation of clinical symptoms, as described in previous reports. Nivolumab is a human immunoglobulin G4 anti-PD-1 monoclonal antibody, by which functionally exhausted T cells in the tumor microenvironment regain antitumor cytotoxicity as well as inducing various immune-related adverse events including arthritis and rheumatic disease.…”
supporting
confidence: 88%
“…Since PMR and RS3PE especially affect the elderly and swelling and pitting edema of the hands and feet are present in 8-12% of PMR patients, it has been suggested that PMR and RS3PE might constitute aspects of the same disease [75]. The etiology of RS3PE is unknown, but IL-6, produced by the synovial tissues, may play a central role in the development of RS3PE, either directly, or through induction of VEGF production, which then leads to synovial hepervascularity and increased vascular permeability [82][83][84]. Corticosteroids still constitute the preferred treatment for RS3PE and in most cases of RS3PE the quick and the dramatic response is one of the characteristics of the disease.…”
Section: Polymyalgia Rheumatica and Remitting Seronegative Symmetricmentioning
confidence: 99%
“…The serum VEGF levels in patients with RS3PE syndrome are significantly higher than those observed in patients with various connective tissue diseases, including RA, systemic lupus erythematosus, mixed connective tissue disease, polymyositis/dermatomyositis and vasculitis syndrome, suggesting that measuring the level of VEGF is useful in the diagnosis and assessment of the disease activity of RS3PE syndrome (2). In addition, we previously reported that subcutaneous edema and tenosynovitis in the extremities in patients with RS3PE syndrome respond to steroid treatment, thus indicating that hand US and MRI are useful tools for detecting subcutaneous edema and synovitis and monitoring the disease activity in patients with RS3PE syndrome (9). In the present case, the high VEGF level and hand MRI and US findings were compatible with the characteristics of RS3PE syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…For these reasons, we diagnosed the patient with 'RA with RS3PE syndrome-like symptoms. ' We previously reported that RS3PE syndrome is charac-terized by an elevated serum VEGF level with multiple and symmetrical tenosynovitis and hypervascularity in the presence of subcutaneous edema of the extremities on MRI and US (2,9). The serum VEGF levels in patients with RS3PE syndrome are significantly higher than those observed in patients with various connective tissue diseases, including RA, systemic lupus erythematosus, mixed connective tissue disease, polymyositis/dermatomyositis and vasculitis syndrome, suggesting that measuring the level of VEGF is useful in the diagnosis and assessment of the disease activity of RS3PE syndrome (2).…”
Section: Discussionmentioning
confidence: 99%